Holograph interferomatery for modelling rate change of shoreline from airsar data - Marghany, Maged; Hashim, Mazlan; Cracknell, Arthur P. (2007)
This work is introducing a new approach for modeling shoreline change rate from AIRSAR Cvv- band. The hologram algorithm has been applied to simulate the wave spectra propagation pattern. In addition, Doppler frequency and azimuth cut off models are used to model longshore current movement and rate change of sediment transport volume. The results show that the phase information of AIRSAR hologram image can be used to simulate the wave refraction pattern. Furthermore, the Shoreline change rate is less than -0.5m /day which indicates an erosion event with accuracy error of plusmn 0.05 m/day.